A climatological study of the wet and dry conditions in the pre‐summer monsoon season of the Philippines. (28th December 2019) - Olaguera, Lyndon Mark P.; Matsumoto, Jun
Abstract: This study investigates the climatology of the wet and dry conditions in the pre‐summer monsoon season of the Philippines that are less emphasized in previous works. Wet cases (Type W), which account for about 23% of the total pre‐summer monsoon days from 1979 to 2015, are identified from April 1 to the monsoon onset defined by the Philippine Atmospheric, Geophysical, and Astronomical Services Administration (PAGASA). The differences between the Type W and dry cases (Type D) are presented. The synoptic conditions associated with the Type W and Type D cases are sub‐divided into two sub‐types based on the wind conditions, the (a) westerly winds at 925 hPa ( WINDS 925hPa ) intrusion over Luzon Island (120°–122.5°E, 12.5°–22°N) (Type WW and Type DW ), and (b) enhanced easterly WINDS 925hPa (Type WE and Type DE ). The Type WE (Type WW ) cases account for about 63.9% (36.1%) of the total Type W cases, while the Type DE (Type DW ) cases account for about 88.1% (11.9%) of the total Type D cases. A subset of Type WE cases (Type WEDef ), which features an eastward propagating cold front to the north of Luzon Island and an intensifying anticyclone to its west originating from the east of the Tibetan Plateau and their differences are also examined. These two opposing circulations interact with the subtropical high over the northern Pacific and the easterlies over Luzon Island, and form a deformation zone. The confluence region of this deformation zone, where the cold front interacts with the warm and humid air brought by the easterly WINDS 925hPa, lies over Luzon Island and contributes to the convective activities during the pre‐summer monsoon over this region. This is the first attempt to clarify and document the role of deformation zones as another synoptic‐scale convective system during the pre‐summer monsoon season of the country. Abstract : Composites of outgoing longwave radiation (OLR; shades; W·m −2 ) and winds at 925 hPa ( WINDS 925hPa ) for wet days associated with clear deformation zones (Type WEDef ) during the pre‐summer monsoon season of the Philippines from 1979 to 2012. The cyclonic and anticyclonic circulations, and deformation zone are denoted as "C, " "A, " and "D", respectively. For "A, " A1 and A2 indicate the anticyclones centred in the NE Pacific and the eastern Eurasia to the west Pacific, respectively.